2005
DOI: 10.1016/j.applanim.2004.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Why in earth? Dustbathing behaviour in jungle and domestic fowl reviewed from a Tinbergian and animal welfare perspective

Abstract: Dustbathing has been the subject of much research in captive birds. In the present review we bring together the studies of domestic fowl (Gallus gallus domesticus) and jungle fowl (Gallus gallus) to provide a more complete picture of the behaviour. Dustbathing is discussed from the four aspects suggested by Tinbergen (1963)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 62 publications
(91 reference statements)
1
75
0
2
Order By: Relevance
“…The blood corticosterone, glucose and triglycerides were lower than respective levels in controls. Olsson & Keeling (2005) and Dixon et al (2008) found that the behaviour of taking dust baths is an important indicator of social welfare of birds. According to Sherwin & Kelland (1998), the higher welfare in turkeys increased the time spent in stretching, feather pecking, and dust bathing.…”
Section: Discussionmentioning
confidence: 99%
“…The blood corticosterone, glucose and triglycerides were lower than respective levels in controls. Olsson & Keeling (2005) and Dixon et al (2008) found that the behaviour of taking dust baths is an important indicator of social welfare of birds. According to Sherwin & Kelland (1998), the higher welfare in turkeys increased the time spent in stretching, feather pecking, and dust bathing.…”
Section: Discussionmentioning
confidence: 99%
“…latency to emerge from a box and response to a tonic immobility test), which was interpreted as a response to the anxiety associated with not performing this maintenance activity. Later, Olsson and Keeling (2005) suggested that the selection operates directly on the fear response because dustbathing is realized only when the bird is not at risk of predation. The pre-laying behaviour of laying hens (sitting activity) is among the rare stereotypes observed in livestock.…”
Section: Genetics Of the Behavioural Response To Changes In The Physimentioning
confidence: 99%
“…It acts to remove skin parasites, regulate the amount of feather lipids, and maintain plumage condition (Olsson and Keeling, 2005). Hens have been found to work to obtain a dustbathing substrate, and after deprivation of dustbathing, are more motivated to dustbathe, indicating that it is a high priority (Widowski and Duncan, 2000).…”
Section: Dustbathingmentioning
confidence: 99%
“…However, the dustbathing sequence cannot be completed, as there is no substrate, nor shaking off lipid-saturated dust. Sham dustbathing lacks positive feedback (Widowski and Duncan, 2000), does not satisfy birds' motivation for dustbathing (Olsson and Keeling, 2005), and indicates a reduced state of welfare (Lay et al, 2011). Further, when birds are unable to dustbathe, plumage is in a poorer condition as it is dirtier, less waterproof and less insulative (Scholz et al, 2014).…”
Section: Dustbathingmentioning
confidence: 99%
See 1 more Smart Citation